2015
DOI: 10.3189/2015jog13j237
|View full text |Cite
|
Sign up to set email alerts
|

Mass-balance changes of the debris-covered glaciers in the Langtang Himal, Nepal, from 1974 to 1999

Abstract: Thick debris cover on glaciers can significantly reduce ice melt. However, several studies have suggested that debris-covered glaciers in the Himalaya might have lost mass at a rate similar to debrisfree glaciers. We reconstruct elevation and mass changes for the debris-covered glaciers of the upper Langtang valley, Nepalese Himalaya, using a digital elevation model (DEM) from 1974 stereo Hexagon satellite data and the 2000 SRTM (Shuttle Radar Topography Mission) DEM. Uncertainties are high in the accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
183
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 161 publications
(203 citation statements)
references
References 67 publications
16
183
4
Order By: Relevance
“…Several recent studies suggested that elevation changes on debris-covered and debris-free glaciers are similar in the Himalayas and Karakoram (Gardelle et al, 2013;Kääb et al, 2012;Pellicciotti et al, 2015). Conversely, Nuimura et al (2012) showed that the debris-covered areas are subject to higher rates of lowering than debris-free areas in Khumbu region, though the 400 m difference in mean elevation between the debriscovered and debris-free areas (5102 and 5521 m a.s.l.…”
Section: Spatial Variability Of Elevation Changes Over the Debris-covmentioning
confidence: 84%
See 1 more Smart Citation
“…Several recent studies suggested that elevation changes on debris-covered and debris-free glaciers are similar in the Himalayas and Karakoram (Gardelle et al, 2013;Kääb et al, 2012;Pellicciotti et al, 2015). Conversely, Nuimura et al (2012) showed that the debris-covered areas are subject to higher rates of lowering than debris-free areas in Khumbu region, though the 400 m difference in mean elevation between the debriscovered and debris-free areas (5102 and 5521 m a.s.l.…”
Section: Spatial Variability Of Elevation Changes Over the Debris-covmentioning
confidence: 84%
“…However, the role played by debris on the surface mass balance of glaciers and, in turn, on the glacier response to climate change remains unclear (Kääb et al, 2012). Indeed, this debris layer insulates the glacier surface from the atmosphere when it reaches a sufficient thickness and complicates the response to climate change compared to clean-ice glaciers (Jouvet et al, 2011;Kirkbride and Deline, 2013;Østrem, 1959;Pellicciotti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The energy balance drives the melt of the debris-covered tongues and several studies point toward a yet unexplained faster surface lowering of the tongues of these glaciers than what can be expected based on the melt suppression by thick debris (Kääb et al, 2012;Gardelle et al, 2013;Pellicciotti et al, 2015;Azam et al, 2018). It is unclear whether this behavior can be attributed to turbulent fluxes, supra-glacial features such as cliffs and ponds, a reduced emergence velocity or other processes (Vincent et al, 2016;Azam et al, 2018).…”
Section: Applications Of Thermal Uav Imagerymentioning
confidence: 87%
“…In addition, features such as meltwater ponds and ice cliffs in the ablation zone absorb significantly more energy than adjacent debris-covered surfaces. These features may give compensatory high melt rates (e.g., Inoue and Yoshida, 1980;Sakai et al, 1998Sakai et al, , 2000Pellicciotti et al, 2014;Immerzeel et al, 2014a) that support using a thinner average or "effective" debris thickness when assigning an average value to each 2 km grid cell in WRF D3.…”
Section: Specification Of Debris Extent and Thickness In Wrf D3mentioning
confidence: 99%